Comparative Outcomes of Different Surgical Techniques for the Removal of Impacted Mandibular Third Molars - Swapnil U. Shinde; Khushboo C. Peswani; Abhilasha Sharma; Swarna Rai; Raj K. Dangi; Neelam Choudhary; Rahul Tiwari (Journal of Pharmacy and Bioallied Sciences)
Introduction: Impacted mandibular third molar removal is a common oral surgery procedure, often associated with postoperative complications. The choice of surgical technique may influence outcomes such as pain, swelling, and healing time. This study aims to compare different surgical techniques to evaluate their impact on clinical outcomes. Methods: A retrospective analysis of patients undergoing impacted mandibular third molar removal was conducted. Three techniques were evaluated: traditional rotary instruments, piezosurgery, and laser-assisted surgery. Postoperative outcomes, including pain, edema, and healing time, were recorded. Results: Patients who underwent piezosurgery reported significantly less postoperative pain and swelling compared to those treated with rotary instruments. Laser-assisted surgery showed a comparable reduction in pain but extended healing time. Conclusion: Piezosurgery is the most favorable technique in terms of minimizing postoperative discomfort and swelling, while laser-assisted surgery may be beneficial in certain clinical scenarios.